Вы находитесь на странице: 1из 1

( x + 4)dx

x 2 2x 8 .

:
x +4
x+4
A
B
A( x + 2 ) + B( x 4 )
=
=
+
=
;
( x 4)( x + 2)
x 2 x 8 ( x 4 )( x + 2 ) x 4 x + 2
x + 4 = A( x + 2 ) + B( x 4 );
1
x = 2; 2 = 6B; B = ;
3
4
x = 4; 8 = 6A; A = .
3
x +4
4
1
1
1
=

2
x 2x 8 3 x 4 3 x + 2
x+4
1
1
1
4
1
4
x 2 2x 8 dx = 3 x 4 3 x + 2 dx = 3 ln x 4 3 ln x + 2 + C.
2

1
4
1
1
1
4( x + 2) x + 4
x +4
4


=
= 2
.
ln x 4 ln x + 2 + C =
3
3 x 4 3 x +2
3( x 4 )( x + 2)
x 2x 8
3

x+4

dx = ln x 4 ln x + 2 + C .
: 2
3
3
x 2x 8